Auditing Government Purchases with a Multicriteria Anomaly Detection Strategy - Maia, Patrícia; Meira Jr., Wagner; Cerqueira, Breno; Cruz, Gustavo (Journal of Information and Data Management, 2020)
Government purchases are the usual instrument for public acquisition of goods and services. Despite extensive legislation, several control and auditing mechanisms, frauds are still diverse and commonplace at all levels of public administration, wasting public resources. Through the use of frequent patterns, temporal correlation and combined analysis of multi-criteria, this work proposes a methodology for detecting anomalies in government purchases. The methodology promotes several levels of filtering with respect to entities involved and purchases are considered as fraudulent based on diverse criteria. The applicability and effectiveness of the methodology is demonstrated through a real case study where we were able to identify a long term provider collusion.